A draft genome sequences and molecular characterisation of glycoprotein B and lower matrix phosphoprotein of rat cytomegalovirus all-3 strain - Quah, Yi Wan (2013)
Congenital cytomegalovirus (CMV) infection causes neurological damages to newborn infants and persists over the years in infants. Rat CMV (RCMV) ALL-03 strain (RCMV ALL-03) was the first RCMV isolated from the placenta and uterus of rat. This RCMV ALL-03 was hypothesised to mimic congenital human CMV (HCMV) infection. Overall, the study signifies the genome characterisation of a novel local transplacental strain RCMV ALL-03, as well as the glycoprotein B (gB) and lower matrix phosphoprotein (pp65) RCMV ALL-03 gene characterisation. The study was commenced by propagating RCMV ALL-03 extensively to a large amount alongside with the reference RCMV English strain (RCMV-E) in rat embryonic fibroblast (REF) cells. Infected cells exhibiting advance cytopathic effect were harvested and concentrated by 8% (w/v) PEG6000. Concentrated viruses were then purified through sucrose gradient. Based on the similarity between HCMV and RCMV ALL-03, monoclonal antibody against gB of HCMV was used to immunoprecipitate RCMV ALL-03 gB through Western blot and immunoperoxidase assay. Likewise, monoclonal antibody pp65 of HCMV was able to immunoprecipitate pp65 of RCMV ALL-03 by immunoperoxidase assay, indicating there are shared homology between HCMV and RCMV ALL-03. The Illumina Genome Analyzer IIx generated a total of 3.8 million paired end sequence reads from multiplexing of both genomic viral DNA libraries. The raw sequencing results were assembled via de novo approach into contigs, producing a total of 6 large CMVrelated contigs for RCMV ALL-03 and 11 large CMV-related contigs for RCMV-E. These contigs were aligned and arranged based on reference RCMV Maastricht strain (RCMV-M), followed by scaffolding into draft genomes. The estimated size of RCMV ALL-03 was 198,895 bp while RCMV strain English was estimated to be 175,071 bp. Phylogenetic tree of RCMV ALL-03 draft genome with other reference CMVs revealed that RCMV ALL-03 belongs to the Muromegalovirus genus and that it is closest to RCMV-E, with an estimated difference of 8.2 substitution per 1 kbp from RCMV-E. Based on gene prediction software GeneMarkS, there were 136 genes predicted for RCMV ALL-03 and 112 genes predicted for RCMV-E. All predicted genes were subjected to BlastX analysis, followed by mapping and annotation of the genes using Blast2Go software. For the RCMV ALL-03, there were 5 genes without any blast hits and a total of 46 genes were annotated. The gB and pp65 genes were among the annotated genes. Phylogenetic analysis of RCMV ALL-03 gB and pp65 showed that RCMV ALL-03 branched individually from other reference CMVs despite having almost similar branch distance as the reference CMVs. By designing and examining the RCMV gB and pp65 specific primers for polymerase chain reaction (PCR) via in silico and lab verification, RCMV ALL-03 gB and pp65 gene were amplified. This study revealed the genome sequence of RCMV ALL-03, which is essential in the understanding of shared homology between RCMV ALL-03 and HCMV. The relatedness of RCMV ALL-03 to RCMVE showed the conserve regions of rodent CMV but their divergence revealed potential RCMV ALL-03 unique transplacental haracteristics. Future exploitation study on the RCMV ALL-03 could help provide a better understanding of congenital HCMV.